Efektivitas Pembelajaran Daring Terhadap Hasil Belajar PAI Di SMP Negeri 3 Rantau Panjang Ogan Ilir - Musaddas, Rahmi (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2022)
The coronavirus (covid-19) has had a considerable impact on education, with the issuance of policies on online learning to prevent the spread of covid-19. The objectives of this study were (1) To determine the effectiveness of online learning in Islamic Education lessons, (2) to determine the learning outcomes of Islamic Education, and (3) to determine the relationship between the effectiveness of online learning in Islamic Education lessons to the learning outcomes of Islamic Education at SMP Negeri 3 Rantau Panjang Ogan Ilir Even Semester 2020-2021 academic year. The research sample consisted of 136 students. This research used quantitative methods with a descriptive approach. The results showed that online learning at SMP Negeri 3 Rantau Panjang Ogan Ilir was quite effective, seen from 69% (94 byondents), even though the online learning application was only WhatsApp. However, these results can only be seen from cognitive knowledge, while PAI lessons were only said to be successful when applied to daily actions. Suggestions from researchers SMP Negeri 3 Rantau Panjang Ogan Ilir should use applications such as: Zoom, google classroom, and e-learning and not only use the WhatsApp application.